The Role of Administrators in Paraprofessional Supervision to Support Ethnic Minority Students with Special Needs - Betty Y. Ashbaker; Jill Morgan (Educational Considerations, 2006)
The No Child Left Behind (NCLB) Act of 2001 provided a clear mandate to school administrators to provide additional training for professional and paraprofessional staff.
Keywords: employment; paraprofessionals; supervision; special needs